Enhancing Students' Listening Skills Using Extensive Reading Central in an Extensive Listening Program - Stella Prancisca; Cary Chappell (Universitas Pendidikan Mandalika, 2026)
This study explores the effectiveness of an Extensive Listening (EL) program using ER Central in improving university students' TOEFL listening comprehension. The program was implemented for one semester with 61 English course students, who underwent pre- and post-tests using the TOEFL listening section. The EL program, inspired by Extensive Reading (ER), emphasized regular exposure to authentic audio materials supplemented with text support. ER Central facilitated material delivery, progress tracking, and quiz administration. Findings revealed a significant improvement in students' listening scores, with an average increase of 26.89 points from pre-test (378.52) to post-test (405.41). A paired t-test confirmed the statistical significance of this improvement (t = -5.085, p < 0.001). However, correlations between the number of quizzes completed, average quiz scores, and score improvements were weak and insignificant, suggesting that frequent quizzes alone may not directly enhance listening comprehension. Pedagogically, the findings suggest that technology-supported extensive listening can promote learner autonomy and consistent practice, especially when aligned with standardized test formats such as TOEFL. Despite its success, limitations include the absence of a control group and the restricted generalizability of results. The findings underscore the need for tailored materials aligned with TOEFL question formats and a holistic approach integrating diverse listening strategies. This research contributes to understanding how technology-enhanced EL programs can optimize language learning outcomes.